Effects of nitrogen- and oxygen-containing functional groups of activated carbon nanotubes on the electrochemical performance in supercapacitors - Liu, Haiyan; Song, Huaihe; Chen, Xiaohong; Zhang, Su; Zhou, Jisheng; Ma, Zhaokun (Journal of power sources, 2015)
A kind of nitrogen- and oxygen-containing activated carbon nanotubes (ACNTs) has been prepared by carbonization and activation of polyaniline nanotubes obtained by rapidly mixed reaction. The ACNTs show oxygen content of 15.7% and nitrogen content of 2.97% (atomic ratio). The ACNTs perform high capacitance and good rate capability (327 F g−1 at the current density of 10 A g−1) when used as the electrode materials for supercapacitors. Hydrogen reduction has been further used to investigate the effects of surface functional groups on the electrochemical performance. The changes for both structural component and electrochemical performance reveal that the quinone oxygen, pyridinic nitrogen, and pyrrolic nitrogen of carbon have the most obvious influence on the capacitive property because of their pseudocapacitive contributions. •Activated carbon nanotubes were prepared using polyaniline as precursor.•The activated carbon nanotubes show high N, O contents and high surface areas.•Both high specific capacitance and rate capability were achieved.•Effects of surface functional groups were investigated by hydrogen reduction.